Assistance of Halal Certification and Sharia Financial Literacy Training for MSME in Bandar Lampung City - Mirza. BR, Aryan Danil; Putra, Joni; Fathia, Syaharani Noer; Septiyanti, Ratna (Penerbit Goodwood, 2023)
Purpose: The need for halal certifications is increasing. People are beginning to care about the halalness of a product, especially in the food and beverage (F&B) industry. In addition, the low level of Islamic financial literacy in the community, especially in MSMEs in Bandar Lampung City, is a strong reason for the service team. Public education about Islamic finance is necessary from an early age, so that people can better understand the concept of Islamic finance and product development and benefits in the last decade. Method: This service uses the concept of mentoring in the form of Focus Group Discussion (FGD) for education and socialization regarding Islamic financial literacy and introduces the morning halal certification process for business actors in the processed food sector. Result: The Community Service Team took the initiative to provide halal certification assistance to MSME partners to increase products. Limitations: This assistance involves only limited MSMEs, and future assistance can involve more MSMEs to obtain a greater impact. Contribution: MSMEs can have more added value and increase their competitive value in the midst of intense business competition.